2013
DOI: 10.1095/biolreprod.112.106708
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Live Germ-Cell Desquamation as a Major Mechanism of Seasonal Testis Regression in Mammals: A Study in the Iberian Mole (Talpa occidentalis)1

Abstract: In males of seasonally breeding species, testes undergo a severe involution at the end of the breeding season, with a major volume decrease due to massive germ-cell depletion associated with photoperiod-dependent reduced levels of testosterone and gonadotropins. Although it has been repeatedly suggested that apoptosis is the principal effector of testicular regression in vertebrates, recent studies do not support this hypothesis in some mammals. The purpose of our work is to discover alternative mechanisms of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
72
2
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 40 publications
(80 citation statements)
references
References 68 publications
5
72
2
1
Order By: Relevance
“…Although there are some species of mammals in which apoptosis is known not to be the main cellular mechanism in testicular regression, its function being the control of proliferation (Blottner et al, 2007;Dadhich et al, 2013), in other animal species it is considered to be the main mechanism involved in this process. Some species like the Brown Hare, in which spermatogenesis arrest, in the non-breeding season, occurs in spermatocytes, only spermatocytes and rarely spermatogonia undergo apoptosis (Strbenc et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there are some species of mammals in which apoptosis is known not to be the main cellular mechanism in testicular regression, its function being the control of proliferation (Blottner et al, 2007;Dadhich et al, 2013), in other animal species it is considered to be the main mechanism involved in this process. Some species like the Brown Hare, in which spermatogenesis arrest, in the non-breeding season, occurs in spermatocytes, only spermatocytes and rarely spermatogonia undergo apoptosis (Strbenc et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, in the white-footed mouse, starling (Young & Nelson, 2001) or the crow (Jenkins et al, 2007;Islam et al, 2012) it has been observed that, in addition to apoptosis in spermatocytes, apoptosis also occurs in round spermatids and spermatogonia, although to a lesser extent, while spermatogenesis arrest, occurs in spermatogonia. To date, the Syrian hamster has been classified as a species where apoptosis is important but not the main mechanism of testicular regression, owing to the lack of data concerning the changes that occur during testicular regression (Dadhich et al, 2013), although it is known that spermatocyte apoptosis is crucial for maintaining regression once it is already established (Morales et al, 2002). In this study, the effect of short photoperiod has been studied throughout the whole process of testicular regression, so that it is possible to conclude that apoptosis plays an essential role in the atrophy of the seminiferous epithelium during the non-breeding season.…”
Section: Discussionmentioning
confidence: 99%
“…The panels in figure 1 depict the aspect of active and inactive testes in 2 mammalian species, the Iberian mole, Talpa occidentalis , and the wood mouse, Apodemus sylvaticus . In both species, the inactive testis maintains some meiotic activity, as meiosis onset is not completely interrupted and some few primary spermatocytes are still present in the regressed seminiferous tubules [Dadhich et al, 2010[Dadhich et al, , 2013. This situation appears to be quite common in many species that undergo seasonal testis regression, as observed in the Japanese redbellied newt, Cynops pyrrhogaster [Yazawa et al, 2000], the silver fox, Vulpes vulpes [Andersen Berg et al, 2001], the Syrian hamster [Morales et al, 2002[Morales et al, , 2007, the Chinese soft-shelled turtle, Pelodiscus sinensis [Zhang et al, 2008], and the Japanese jungle crow, Corvus macrorhynchos [Islam et al, 2012], as well as in the Mediterranean pine vole, Microtus duodecimcostatus [unpubl.…”
Section: Circannual Testis Alterations Derived From Seasonal Breedingmentioning
confidence: 99%
“…The structure and functionality of the BTB has been investigated in 3 seasonally breeding mammals: the mink, Mustela vison [Pelletier, 1988], the Djungarian hamster, Phodopus sungorus [Tarulli et al, 2008], and the Iberian mole [Dadhich et al, 2013]. Molecular-tracer experiments have shown that in all 3 species the BTB becomes permeable in the non-breeding period, allowing the tracer to reach the adluminal compartment of the seminiferous epithelium ( fig.…”
Section: Circannual Testis Alterations Derived From Seasonal Breedingmentioning
confidence: 99%
See 1 more Smart Citation